Exosomal miR‑3681‑3p from M2‑polarized macrophages confers cisplatin resistance to gastric cancer cells by targeting MLH1 - Wei, Wujun; Li, Jiaxing; Huang, Jingjing; Jiang, Qi; Lin, Cheng; Hu, Rentong; Wei, Jiazhu; Li, Qiao; Xu, Guidan; Chang, Zhengyi (Molecular medicine reports, 2025)
Cisplatin (DDP) is a key chemotherapeutic agent in the treatment of gastric cancer; however, its efficacy is often limited by chemoresistance, a notable challenge in clinical oncology. The present study aimed to investigate the influence of exosomes derived from M2-polarized macrophages, which promote this resistance, on the response of gastric cancer cells to DDP, examining both the effects and the underlying mechanisms. M2 macrophages, differentiated from mouse bone marrow cells with interleukin (IL)-13 and IL-4, were identified using immunofluorescence staining for CD206 and CD163. Exosomes derived from these macrophages were characterized using transmission electron microscopy and protein markers, including calnexin, tumor susceptibility gene 101 and CD9. The role of exosomal microRNA (miR)-3681-3p in DDP resistance was assessed using Cell Counting Kit-8 and apoptosis assays, while a luciferase reporter assay was used to elucidate the interaction between miR-3681-3p and MutL protein homolog 1 (MLH1). Co-culturing gastric cancer cells with M2 macrophages enhanced DDP resistance, an effect amplified by exosomes from M2 macrophages enriched with miR-3681-3p. This microRNA directly targeted and reduced MLH1 protein expression. Overexpression of miR-3681-3p through mimic transfection, along with MLH1 silencing by small interfering RNA transfection, significantly increased DDP resistance, as evidenced by elevated IC50 values in AGS cells. By contrast, the overexpression of MLH1 effectively reversed the drug resistance of AGS cells to DDP caused by miR-3681-3p mimic transfection, as evidenced by a decrease in the IC50 value. In conclusion, exosomal miR-3681-3p from M2 macrophages may have a key role in conferring DDP resistance to gastric cancer by suppressing MLH1, offering a new therapeutic target for overcoming chemoresistance.